Essentials of medical geology : impacts of the natural environment on public health - Selinus, O.; Alloway, B. J. (Elsevier Academic Press, 2005)
This authoritative reference volume emphasizes the importance and interrelationships of geological processes to the health and diseases of humans and animals. Its accessible format fosters better communication between the health and geoscience communities by elucidating the geologic origins and flow of toxic elements in the environment that lead to human exposure through the consumption of food and water. For example, problems of excess intake from drinking water have been encountered for several inorganic compounds, including fluoride in Africa and India; arsenic in certain areas of Argentina.